Comparison of coupled-channel studies of nucleon scattering from oxygen isotopes with the shell model - Karataglidis, S.; Svenne, P.; Amos, K.; Canton, L.; Fraser, Paul; van der Knijff, D. (2015)
The structures of 17O and 17F are studied via the Multi-Channel Algebraic Scattering (MCAS) method, which describes low-energy nucleon-nucleus scattering with a collective model specification for the target states. The model allows for the incorporation of the Pauli Principle in the interactions describing the scattering and the formation of the compound states. The collective model in the current version of MCAS can be either rotational or vibrational, and we utilise a vibrational model specification of the spectrum of 16O to obtain the states in the mass-17 systems. Comparison is made with results from large-scale multi-¯hw shell model calculations for the mass-17 nuclei. Results for the spectra of mass-19 nuclei, formed by the coupling of a nucleon from 18O, from both the shell model and MCAS are also presented.